Awareness among mothers regarding oral rehydration salt solution in management of diarrhea: A cross-sectional study - Thammanna, P S; Sandeep, M; Sridhar, P V (Indian Journal of Child Health, 2015)
Background: Diarrhea remains one of the leading global causes of death among children under the age of 5 years; diarrhea and the resultant mortality from it is both preventable and treatable. Proper knowledge regarding the use of oral rehydration salt solution (ORS) helps in preventing morbidity and mortality from diarrhea. Objective: To assess the awareness, knowledge and practice of mothers of under-five children regarding the use of ORS and other alternative solution during diarrheal illness. Methods: A cross-sectionalstudy involving 250 mothers with children of age 6 months - 5 years was carried out. Data were collected using a semi-structured questionnaire; it included data regarding socio-demographic characteristics and questions pertaining to knowledge of mothers about ORS. Results: Out of 250 study participants, 203 (81.2%) mothers were homemakers and 212 (84.8%) were literate. It was seen that 63 (25.2%) mothers did not know about ORS, 146 (58.4%) knew about the role of ORS in diarrhea, 129 (51.6%) had knowledge regarding homemade ORS. Only 119 (47.6%) mothers knew how to prepare ORS properly, and the most common source of informationregarding ORS was a doctor. 84 (33.6%) mothers had a misconception about ORS, and only 51 (20.4%) participants knew about syrup zinc. The higher education level of mother was associated with better knowledge regarding various aspects of oral rehydration therapy. Conclusion: The knowledge regarding the use of ORS in diarrhea is insufficient; hence, there is need to educate mothers regarding the use of ORS as well as homemade ORS substitutes during diarrhea.